ANALISIS DAMPAK SOSIAL EKONOMI PEMBANGUNAN BREAKWATER PADA KOMUNITAS PESISIR DI PELABUHAN PERIKANAN BEBA, TAKALAR, SULAWESI SELATAN - M Irham Ilyas; Andi Tenri Fada; Kasri Kasri; Sitti Fakhriyyah (JURNAL AKUAKULTUR, TEKNOLOGI DAN MANAJEMEN PERIKANAN TANGKAP, ILMU KELAUTAN, 2025)
Breakwater construction in coastal areas is essential for enhancing port stability and ensuring the safety of fisheries activities; however, the construction phase often generates socio-economic pressures on communities dependent on port operations. This study aims to analyze the impacts of breakwater development at Beba Fishing Port, Takalar District, with a focus on changes in fishermen’s income, local economic dynamics, and social disturbances during construction. The research employs a mixed-methods approach with an explanatory sequential design, which integrates quantitative and qualitative analyses in a sequential manner. The initial phase involved a survey of 40 respondents—including fishermen, fish traders, small-scale entrepreneurs, and nearby residents—followed by in-depth interviews and field observations based on Participatory Action Research. Chi-square analysis was used to assess the relationship between demographic characteristics and levels of impact. The findings indicate that fishermen’s income decreased by 11% during construction due to operational disruptions at the port but increased by 6% after the breakwater became fully functional. Economic impacts were more pronounced among fishermen and fish traders (χ² = 8.0; p < 0.05). Socially, communities experienced conflict, pollution, and environmental discomfort, particularly in areas affected by heavy-equipment traffic. Inferential analysis revealed significant associations between age (χ² = 11.73; p < 0.01) and education level (χ² = 8.10; p < 0.05) and conflict experiences, with younger and less-educated groups being the most affected.